Investigating cascading events for emergency departments in Baltimore City using a two-state Markov model. (December 2021) - Zhang, Xu; Golden, Bruce; Wasil, Edward; Pimentel, Laura; Hirshon, Jon Mark
Abstract: The event of high emergency department (ED) utilization or inaccessibility to the ED may result in hospital after hospital in a city not accepting new patients in need of urgent medical care. We call this a cascading event. In this paper, we investigate cascading events among 11 EDs in Baltimore City in 2018 and 2019 using a two-state Markov model. Additionally, the transition probabilities are used to monitor the evolution of cascading events. Meanwhile, we predict the expected remaining hours in each state. After we calculate and compare the probabilities of having a cascading event for each ED, we finally identify the similarity and heterogeneity among EDs using cluster analysis. The findings of our study reveal that the continuous yellow alerts at Johns Hopkins Hospital, Johns Hopkins Bayview Medical Center (JH Bayview), Sinai Hospital, and the University of Maryland Medical Center (UMMC) are associated with a large chance of having a cascading event in the city that affects all 11 hospitals. Weekdays dramatically increased chances of having a cascading event.